ANALISIS SELF-DISCLOSURE GEN Z PADA CLOSE FRIEND INSTAGRAM: STUDI RUANG PRIVAT DI MEDIA SOSIAL - Fardianti, Amelia; Tuti Bahfiarti; Indrayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of social media has changed the way the younger generation builds social relationships and expresses themselves. One of the most widely used features is close friends on Instagram, which allows users to create semi-public private spaces to share more personal things. This study focuses on the self-disclosure patterns of Generation Z aged 18–25 years through the use of these features, emphasizing the reasons for self-disclosure, audience selectivity strategies, and the consequences caused. The research method uses a qualitative approach with in-depth interview techniques with a number of informants from generation Z aged 18–25 years. The data were analyzed thematically to identify the patterns, meanings, and dynamics of self-openness in a digital context. The results of the study show that the close friend feature is interpreted by Generation Z as a safe space to vent, express emotions, channel humor, and seek social validation without having to worry about being seen by a wide audience. Audience selectivity is the main strategy, where informants only select certain individuals who are considered trustworthy. The conclusion of the study is that close friends function as a private space on social media for Generation Z aged 18–25 years, but the self-openness that occurs is still negotiated between the need to maintain privacy and the urge to build social relationships. Keywords: Self-Disclosure, Gen Z, Close Friend, Instagram, Privacy